Klippel-Trenaunay Syndrome : Radiological Aspect - Badhan, Rajesh K; Bhatti, Varinder Singh; Singh, Gurpreet (GMC Patiala Journal of Research and Medical Education, 2022)
Klippel – Trenaunay Syndrome (KTS) is a rare complex congenital angio-osteo-hypertrophic syndrome. Features of KTS are Capillary Malformation, Soft Tissue/Bone Hypertrophy and Varicose Veins or Venous Malformation (1, 2). The lower extremity is the site of involvement in approximately 95% of patients (3).